2022
DOI: 10.1186/s12951-022-01568-6
|View full text |Cite
|
Sign up to set email alerts
|

Dancing in local space: rolling hoop orbital amplification combined with local cascade nanozyme catalytic system to achieve ultra-sensitive detection of exosomal miRNA

Abstract: The exosomal miRNA (exo-miRNA) derived from tumor cells contains rich biological information that can effectively aid in the early diagnosis of disease. However, the extremely low abundance imposes stringent requirements for accurate detection techniques. In this study, a novel, protease-free DNA amplification strategy, known as “Rolling Hoop Orbital Amplification” (RHOA), was initially developed based on the design concept of local reaction and inspired by the childhood game of rolling iron ring. Benefiting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previous studies have showed that miRNAs exert their roles by negatively modulating target genes' expression and function [34][35][36]. Therefore, the downstream target genes of miR-5000-3p were predicted using a series of target gene prediction programs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that miRNAs exert their roles by negatively modulating target genes' expression and function [34][35][36]. Therefore, the downstream target genes of miR-5000-3p were predicted using a series of target gene prediction programs.…”
Section: Discussionmentioning
confidence: 99%